Research Skills in Primary School Students Formation: Developmental and Competence Impact - Beisenbayeva, Aigul M.; Abildina, Saltanat K.; Feizuldayeva, Saltanat A.; Kopbalina, Kamshat B.; Kurmangaliyeva, Zhanargul K. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The level of research skills of children with inclusion depends on the teacher’s research competencies. To develop them, a future teacher must constantly conduct research and practical work in his own learning process. Background: The formation of research competence in primary school children with disorders is formed on the basis of a common desire for knowledge of the world, due to age-related characteristics and social conditions of education. The task of a teacher in this vein is not only to structure the cognitive interest of younger students but also to integrate educational research competence into the age group. Method: In preparing the study, students were required to deeply analyse information regarding the state of the issue, a comparative description of various modelling options and research methods, an analysis of their advantages, disadvantages, and the choice of a model and research method that would be adequate to the assigned tasks. Results: Future teachers’ willingness to present the teaching material is considered, and also the willingness to raise discussion questions and thus form additional research material. The authors of the article show that such competence is formed in the process of formation of general research competence and can be expressed in a number of definitions that require additional training of a future teacher. Conclusion: There is a need to form research competency directly with teachers, who shape the future research qualities of “special” schoolchildren, which in turn forms the future of a scientific nature.